darkmatter: Racial Reconfigurations and Networked Knowledge Production - Ashwani Sharma; Sanjay Sharma (tripleC: Communication, Capitalism & Critique)
In the form of a discussion the founding editors of darkmatter journal reflect on the challenges of developing an online race project in the neoliberal context of knowledge production. The independent open access journal, operating at the borders of academia and cultural production, attempts to grasp the shifting contours of contemporary race and racism in a networked postcolonial world. Against the limitations of solely working within disciplines such as Postcolonial or Cultural Studies, darkmatter brings into dialogue a diverse range of conceptual frameworks to address the proliferation of race discourses. Interrogating and reworking the developments in digital publishing, the project constructs a space for the exploration and dissemination of race thinking and creating relations between different fields, sites and groups. The threats posed by the info-colonialism of corporate academic publishing are transversed through the evolution of darkmatter with its experiments in techno-cultural design and innovations in autonomous working practices.